2021
DOI: 10.3390/ijms22073350
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Adipose-Derived Stem Cell-Based Self-Assembled Scaffold under Hypoxia and Mechanical Stimulation for Urethral Tissue Engineering

Abstract: Long urethral strictures are often treated with autologous genital skin and buccal mucosa grafts; however, risk of hair ingrowth and donor site morbidity, restrict their application. To overcome this, we introduced a tissue-engineered human urethra comprising adipose-derived stem cell (ASC)-based self-assembled scaffold, human urothelial cells (UCs) and smooth muscle cells (SMCs). ASCs were cultured with ascorbic acid to stimulate extracellular matrix (ECM) production. The scaffold (ECM) was stained with colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
2
7
1
Order By: Relevance
“…Terefore, as 90% of produced collagen is COL I [50], the efect of A2P in scPLCL A2P seems to be associated with the COL I maturation rather than in the mRNA expression. Previously, supplemented AA or its derivatives have been shown to increase the collagen production in hASCs and bone marrow-derived stem cells [53,55,58,81], and similarly to our fndings, COL III mRNA but not COL I mRNA expression was increased in A2P-supplemented osteoblasts [97]. However, Yu et al reported an increase in both total collagen and COL I mRNA amounts in hASCs cultured with supplemented A2P [53].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Terefore, as 90% of produced collagen is COL I [50], the efect of A2P in scPLCL A2P seems to be associated with the COL I maturation rather than in the mRNA expression. Previously, supplemented AA or its derivatives have been shown to increase the collagen production in hASCs and bone marrow-derived stem cells [53,55,58,81], and similarly to our fndings, COL III mRNA but not COL I mRNA expression was increased in A2P-supplemented osteoblasts [97]. However, Yu et al reported an increase in both total collagen and COL I mRNA amounts in hASCs cultured with supplemented A2P [53].…”
Section: Discussionsupporting
confidence: 88%
“…Even though A2P enhanced the hASC proliferation in our study, too high concentrations of AA or A2P in cell culture have been suggested to lead to cytotoxicity and reduced viability [58,81,91], although contradictory reports have been published. For hASCs, cytotoxicity of supplemented A2P appears to be dose-dependent and could be prevented by increasing the cell density.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…A nutrient mixture containing AA also inhibited secretion of MMP-9 monomer and dimer in a broad set of cancer cell lines [75], and similar MMP inhibitory activity has been observed in other human and animal models [76,77]. The effects of AZ-stabilized THDC observed in this study thus appear consistent with prior work demonstrating links between AA release, collagen synthesis, and MMP inhibition [4,5,[71][72][73][74][75][76][77][78].…”
Section: Discussionsupporting
confidence: 88%
“…From this point of view, the ASC-assembly scaffold is more advantageous in repairing urethral tissue [ 36 ]. Rashidbenam et al [ 37 ] co-cultured ASCs with vitamin C to stimulate ECM production. Then, the ASC sheet seeded with urothelial and smooth muscle cells was used as a scaffold.…”
Section: Advances In Ascs Therapy For the Lower Urinary Tractmentioning
confidence: 99%